4CPS-069 Impact of implementing a global collaborative physician-pharmacist strategy on prophylactic antibiotic practices in a university hospital centre. (March 2019) - Pardo, A; Demeester, R; Rivolta, M; Joris, M; Stenuit, S
Abstract : Background: Among different approaches to prevent surgical site infections, antibiotic prophylaxis is substantially important. According to previous published papers, surgical antibiotic prophylaxis (SAP) practices could be optimised by the implementation of isolated strategies. Purpose: To identify risk factors associated with non–compliance towards prophylactic antibiotic guidelines. To test the impact of a combined intervention strategy on compliance towards prophylactic antibiotic guidelines. Material and methods: A quasi-experimental study with a pre-test–post-test evaluation was carried out on five types of intervention: hip prosthesis, coronary artery bypass grafting, colorectal surgery, transurethral resection of the prostate and endoscopic retrograde cholangiopancreatography. Compliance with guidelines was evaluated in 11 criteria within the pre-test and intervention groups. In order to identify risk factors associated with non–compliance, a retrospective observational transversal study was carried out in the pre–test group using a multivariate statistical analysis (Wald test). Odds ratios for the relationships between each independent variable and the outcome variable were then determined. We tested a combined intervention strategy that included: the pre–operative delivery of nominative kits containing the antibiotics with a recommendation paper adapted to patient factors; a pharmacist participating in antibiotic stewardship team for compilation of guidelines and their distribution for implementation; audits; feedback; educational seminar and outreach visits; and the development of an internal computer–based decision tool. For comparison between the two groups (pre–test and intervention groups), data were analysed using χ 2 and t tests for, respectively, categorical and continuous data. Results: The pre-test group (11 January 2016 – 22 April 2016) and the intervention group (9 January 2017 – 21 April 2017) included, respectively, 130 and 118 interventions. The multivariate statistical analysis showed, as in previous studies, that true penicillin allergy, certain types of surgery and some practitioners were associated with non–compliance within the pre–test group. Compared with the pre–test group, the compliance was significantly increased in the test group for all 11 criteria (P<0.05) and in terms of global compliance (42.4% vs 16.9%; P<0.001). This positive impact revealed a culture change, an interest and an awareness observed within the practitioner's teams. Conclusion: This study shows that optimisation of SAP practices is achievable within a proactive multidisciplinary approach. Reference and/or acknowledgements: Wiffen P. Eur J Hosp Pharm 2018;25:1. https://ejhp.bmj.com/content/25/1/1 No conflict of interest.